Perangkat Pembelajran Materi Barisan dan Deret Berbasis Problem Based Learning Guna Memfasilitasi Kemampuan Pemecahan Masalah Matematis Siswa Kelas XI SMA/MA - Endang Hariani; Maimunah Maimunah; Putri Yuanita (Mathematics Education Study Program, 2023)
Learning geometry is an important lesson because it is studied at every level of education and geometry is a sub-matter in mathematics that is very closely related to the lives of students. However, field data shows that there are still many students who experience learning difficulties in geometry material, both obstacles that are classified as ontogenic obstacles, epistemological obstacles and didactical obstacles. This study aims to identify how the distribution of research that addresses learning barriers in Didactical Design Research research on geometry material and also aims to find out what learning barriers students often experience when studying geometry. The research method used is a Systematic Literature Review using 25 articles that have been published in indexed journals Sinta and Scopus in the 2019-2023 period. The article was obtained from search results on the Google Scholar and ERIC data base. The results of this study indicate that research discussing learning barriers in geometry material is mostly carried out at the elementary school level with the sub-material that is most often discussed is two-dimensional material. The results of this study also show that students still experience many types of learning barriers including ontogenic obstacles, epistemological obstacles, and didactical obstacles.